TINGGINYA DURASI SCREEN TIME BERHUBUNGAN DENGAN POLA KONSUMSI DAN PERILAKU MAKAN BALITA USIA 3-5 TAHUN DI JABODETABEK - Putri, Mayra; Humayrah, Wardina (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Screen time is time spent in front of a screen, such as watching TV and playing on a mobile phone. High screen time at 3-5 years can affect consumption patterns and eating behavior. Objectives: To determine the relationship between screen time and consumption patterns and eating behavior in toddlers aged 3-5 years in Jabodetabek.Methods: This study used a cross sectional study design measured by Google Form with 102 toddlers aged 3-5 years. The questionnaires used included: CEBQ (Children Eating Behavior Questionnaire), PFSQ (Parental Feeding Style Questionnaire) and SQ-FFQ (Semi Quantitative Food Frequency Questionnaire). Statistical tests used t-test and Spearman rank correlation test.Results: There was no significant difference in the duration of eating with utensils between toddlers with housewives and toddlers with working mothers (>90 minutes/day). However, there was a significant difference (p=0.001) in the duration of meals without gadgets, with toddlers with working mothers eating about 8 minutes longer than toddlers with housewives. In general, the duration of toddlers' meals without gadgets was 60 minutes shorter than with gadgets. For both working mothers and housewives, there was a significant relationship between meal duration and screen time use on toddlers' eating behaviour in terms of slowness in eating (p = 0.047, r = 0.256) and emotional undereating (p = 0.001, 0.512). And there is a relationship between meal duration and screen time use on animal protein consumption (p=0.003, r=0.448).Conclusion: The more screen time a toddler has, toddlers tend to have slow eating, reduced appetite, and consume more animal side dishes than other food groups.Keywords: consumption patterns; eating behavior; screen time; toddler ABSTRAKLatar belakang: Screen time merupakan waktu yang dihabiskan di depan layar seperti menonton TV dan bermain handphone. Tingginya screen time pada usia 3-5 tahun dapat mempengaruhi pola konsumsi dan perilaku makan. Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan screen time terhadap pola konsumsi dan perilaku makan pada balita usia 3-5 tahun di Jabodetabek. Metode: Penelitian ini menggunakan desain cross sectional studi yang diukur dengan Google Form dengan 102 balita usia 3-5 tahun. Kuesioner yang digunakan antara lain: CEBQ (Children Eating Behavior Questionnaire), PFSQ (Parental Feeding Style Questionnaire) dan SQ-FFQ (Semi Quantitative Food Frequency Questionnaire). Uji statistik menggunakan uji beda dan uji korelasi Rank Spearman.Hasil: Tidak ada perbedaan signifikan pada lama makan balita yang menggunakan gadget baik pada balita yang mempunyai ibu rumah tangga dan ibu bekerja (>90 menit/hari). Namun, terdapat perbedaan signifikan (p=0,001) pada durasi makan tanpa gadget. Balita dengan ibu bekerja makan sekitar 8 menit lebih lama dibandingkan dengan balita dengan ibu rumah tangga. Secara umum, lama makan balita tanpa gadget jauh lebih cepat selama 60 menit dibandingkan dengan gadget. Baik pada ibu bekerja maupun ibu rumah tangga, terdapat hubungan signifikan antara durasi makan dengan penggunaan screen time terhadap perilaku makan balita pada aspek slowness in eating (p= 0,047, r= 0,256) dan emotional undereating (p=0,001, 0,512). Terdapat hubungan antara durasi makan dengan penggunaan screen time terhadap konsumsi protein hewani (p=0,003, r=0,448).Simpulan: Semakin tinggi penggunaan screen time balita maka balita cenderung berperilaku makan lambat dan kurang memiliki keinginan untuk makan, selain itu balita lebih banyak mengonsumsi/mengemil lauk hewani dibandingkan kelompok pangan lain.Kata Kunci: balita; perilaku makan; pola konsumsi; screen time